2004
DOI: 10.4319/lo.2004.49.6.2105
|View full text |Cite
|
Sign up to set email alerts
|

Responses of elemental and biochemical composition of Chaetoceros muelleri to growth under varying light and nitrate : phosphate supply ratios and their influence on critical N: P

Abstract: The critical nitrogen-to-phosphorous ratio (N : P) defines the transition between N and P limitation of growth rate and is not a biological constant. To test the effect of environmental conditions on the critical N : P, we cultured the diatom Chaetoceros muelleri in chemostats with inflow nitrate : phosphate ratios ranging from 5 to 90 mol N (mol P)Ϫ1 at two photon flux densities (PFDs; 50 and 700 mol photons m Ϫ2 s Ϫ1). The nitrate : phosphate ratio marking the transition between N and P limitation increased … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
69
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(77 citation statements)
references
References 43 publications
6
69
2
Order By: Relevance
“…The ranges spanned by these two indicators fit reasonably well with observed ranges of critical N:P supply ratios in phytoplankton cultures (for example, Terry and others 1985;Leonardos and Geider 2004). Although threshold N:P supply ratios are known to differ among species and also to be strongly influenced by growth conditions (Leonardos and Geider 2004), it seems reasonable to interpret both the DIN:DIP and BAN:BAP concentration ratios as proxies for the actual N:P supply ratios experienced by the initial plankton communities in our experiments.…”
Section: Performance Of Nutrient Limitation Indicatorssupporting
confidence: 55%
“…The ranges spanned by these two indicators fit reasonably well with observed ranges of critical N:P supply ratios in phytoplankton cultures (for example, Terry and others 1985;Leonardos and Geider 2004). Although threshold N:P supply ratios are known to differ among species and also to be strongly influenced by growth conditions (Leonardos and Geider 2004), it seems reasonable to interpret both the DIN:DIP and BAN:BAP concentration ratios as proxies for the actual N:P supply ratios experienced by the initial plankton communities in our experiments.…”
Section: Performance Of Nutrient Limitation Indicatorssupporting
confidence: 55%
“…Briefly, PSII photosynthetic unit sizes were determined from O 2 -flash yield measurements using a custom-built LED flash system (Suggett et al 2003). Pigment concentrations were measured by high-performance liquid chromatography (HPLC) via identification and co-elution with pigment standards (see Leonardos & Geider 2004). Finally, PSII fluorescence excitation spectra (400 to 715 nm) were measured with the monochromator on the detector set to 730 nm emission (F 730 ) upon samples pre-treated with DCMU (Lutz et al 2001, Suggett et al 2004.…”
Section: Methodsmentioning
confidence: 99%
“…1). Here, high light grown cells were allowed to grow at a higher dilution (growth) rate than were low light grown cells (Leonardos & Geider 2004). Lower values of F v /F m were not observed at the lower growth rates, but for cells grown under higher growth PFDs (at the higher growth rate).…”
Section: Frr Fluorescence Under Unbalanced Versus Balanced Growthmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, high nutrient and COD concentrations are still found near its estuary, even though the river has been dammed. In most marine environments, nitrogen appears to be the limiting factor of primary production; accordingly, the concentration of TIN, PO 4 -P and molar N/P ratio can control the pattern and function of the ecosystem of a bay, as well as alter the structure, production, and biomass of phytoplankton (Balode et al, 1998;Lenton and Watso, 2000;Leonardos and Geider, 2004;McQuatters-Gollop et al, 2007). However, more N than P entered Sishili Bay from terrestrial sources during rainfall events, as indicated by the increasing trend of TIN concentrations during precipitation.…”
Section: Ecological Status During Red Tides Periodsmentioning
confidence: 99%